2023
DOI: 10.21203/rs.3.rs-2484531/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symmetry Broken Josephson Junctions and Superconducting Diodes in Magic Angle Twisted Bilayer Graphene

Abstract: The simultaneous co-existence and gate-tuneability of the superconducting (SC), magnetic and topological orders in magic angle twisted bilayer graphene (MATBG) open up entirely new possibilities for the creation of complex hybrid Josephson junctions (JJ). Here we report on the creation of gate-defined, symmetry broken Josephson junctions in MATBG, where the weak link is gate-tuned close to the correlated state at a moirĂ© filling factor of 𝛖 = -2. A highly unconventional Fraunhofer pattern emerges, in which su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Current flow in electronic devices can be asymmetric with bias direction, a phenomenon underlying the utility of diodes 1 and known as non-reciprocal charge transport 2 . The promise of dissipationless electronics has recently stimulated the quest for superconducting diodes, and non-reciprocal superconducting devices have been realized in various non-centrosymmetric systems [3][4][5][6][7][8][9][10] . Here we investigate the ultimate limits of miniaturization by creating atomic-scale Pb-Pb Josephson junctions in a scanning tunnelling microscope.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current flow in electronic devices can be asymmetric with bias direction, a phenomenon underlying the utility of diodes 1 and known as non-reciprocal charge transport 2 . The promise of dissipationless electronics has recently stimulated the quest for superconducting diodes, and non-reciprocal superconducting devices have been realized in various non-centrosymmetric systems [3][4][5][6][7][8][9][10] . Here we investigate the ultimate limits of miniaturization by creating atomic-scale Pb-Pb Josephson junctions in a scanning tunnelling microscope.…”
mentioning
confidence: 99%
“…Although two or more Josephson junctions combined into superconducting quantum interference devices (also known as SQUIDS) have long been proposed as amplifiers and rectifiers 13,14 , experiments on single Josephson junctions have only recently observed non-reciprocal behaviour. Baumgartner et al 6 used a proximity-coupled two-dimensional electron gas with strong spin-orbit interaction, Pal et al 7 observed diode-like behaviour in superconducting junctions in proximity to a topological semimetal and Diez-Merida et al 8 in twisted bilayer graphene. Although these devices required external magnetic fields to induce the diode effect, Wu et al 10 demonstrated rectification in a NbSe 2 /Nb 3 Br 8 /NbSe 2 junction without magnetic fields 15 .…”
mentioning
confidence: 99%
“…However, the recent interest is driven by the search of novel materials that break both the inversion and time-reversal symmetry, thereby intrinsically enabling the superconducting diode effect (SDE). Such materials have indeed been experimentally identified and investigated, ranging from metallic films and proximitized semiconductors to van der Waals heterostructures. − While this direction offers a probe into the symmetry properties of novel materials, the resulting devices typically have limited diode efficiency, which is defined as a ratio of supercurrent in the forward and backward directions.…”
mentioning
confidence: 99%